ANALISIS KESESUAIAN LAHAN TAMBAK UNTUK BUDIDAYA IKAN KERAPU DI KOTA TARAKAN - Ery Gusman (Jurnal Harpodon Borneo, 2016)
The purposes of this research was analyzing the feasibility level of brackish ponds for grouper culture at tarakan city.  This research has been sampling for 6 point of brackish pond representing of Tarakan City, there were 2 point at North of Tarakan, 2 point at West of Tarakan and the last at 2 point at East of Tarakan.  Research was processing from September until November 2014.  Sand quality variable was observed were Sand Texture, Organic Matters, pH, Potential Redox, and Fe.  Water quality variable are Temperature, Salinity, pH, Dissolved Oxygen (DO), Ammonia, Nitrite, Nitrate, Phosphate, BOD5, Fe, TSS and Organic Matters.  To resulting the feability of Brackish for grouper, qualitative methods were used, then analysed by matching method to resulting the feasibility class of brackish pond.  Based on the feasibility class of brackish pond analysis for grouper, the result showed that the pond located at North Tarakan, West Tarakan and East Tarakan are in S2 level Group (Fair enough).  Limiting factor that really need to attenting are Fe dan pH of sand, because under feasible in N1 Category (not feasible), although other limiting factor that were almost feasible are Temperature, Ammonia (NH3), BOD and TSS.Keywords : Feasibility Study, Ponds, Grouper, Tarakan.